DESIGN AND STRENGTHENING METHODS FOR FOUNDATIONS OF HYDRAULIC STRUCTURES - Khalimov Ibrokhimjon (Modern American Journals, 2025)
This article provides a comprehensive scientific review and critical analysis of modern approaches to the design and strengthening of foundations for hydraulic structures—including dams, weirs, canals, pumping stations, and retaining walls—under a range of geotechnical, hydraulic, and climatic conditions. Integrating international codes, advanced soil and structural mechanics, regional case studies (with particular reference to Uzbekistan and Central Asia), and state-of-the-art material and monitoring technologies, the article explores the evolution of foundation engineering practice from traditional methods to high-tech solutions for safety, durability, and sustainability. Topics include foundation soil investigation and characterization, load transfer and failure mechanisms, design for static and seismic loads, waterproofing and seepage control, ground improvement and reinforcement methods, monitoring and maintenance, and adaptive solutions for challenging environments such as soft soils, seismic zones, and aggressive groundwater. Special attention is given to risk assessment, digital tools (including FEM modeling and instrumentation), sustainability criteria, and cost-effectiveness. The article concludes with best-practice recommendations for engineers, decision-makers, and researchers involved in the lifecycle management of hydraulic infrastructure.
Keywords: Hydraulic structures; foundation design; soil-structure interaction; ground improvement; geotechnical engineering; seepage control; strengthening methods; monitoring; Uzbekistan; sustainability.